Instructional methods and languages in class: A comparison of two teaching approaches and two teaching languages in the field of intercultural learning. (April 2016) - Busse, Vera; Krause, Ulrike-Marie
Abstract: The article presents the results of a quasi-experimental intervention study with a 2 × 2 factorial design. We implemented a problem-based intercultural learning unit in four secondary schools (grades 9 to 12) and varied the teaching approach (analytical/affective-experiential) and the language of instruction (German/English). The learning unit covered six 45-min lessons and was conducted in nine school courses ( n = 143). Five additional school courses ( n = 66) served as a control group. In all experimental groups, students engaged with critical incidents. These were either analysed (analytical focus) or acted out as role plays (affective-experiential focus). In addition, students analysed film clips (analytical focus) or participated in a simulation game (affective-experiential focus). The experimental groups outperformed the control group in the post-test, which required the analysis of critical incidents. Both teaching approaches were equally effective; however, students evaluated affective-experiential learning more positively. Using a foreign language for teaching did not impair performance. Highlights: Intercultural learning can effectively be stimulated by problem-based approaches. Both instructional foci– affective-experiential vs. analytical– proved effective. The affective-experiential focus was more motivating. Simulation games and film material may be useful additions to critical incidents. Teaching through a foreign language did not impair content acquisition.